Tolerability of Topical Treatments for Atopic Dermatitis - Draelos, Zoe D. (Dermatol Ther (Heidelb), 2019)
Atopic dermatitis (AD) is a common inflammatory skin disease that is accompanied by increased sensitivity to itch-provoking and pain-provoking stimuli. Patients with AD experience skin pain before initiation of therapy and have also reported painful application site reactions in clinical trials of emollients and prescription topical therapies, including topical corticosteroids (TCSs), topical calcineurin inhibitors (TCIs), and a topical phosphodiesterase 4 (PDE4) inhibitor. To compare the sensory tolerability of prescription topical therapies for AD, a comprehensive literature search and analysis of published clinical trials was conducted. Sensory tolerability issues such as application site pain, burning, stinging, and pruritus were often among the most common adverse events or treatment-related adverse events in clinical trials for prescription topical therapies. Tolerability issues occurred at highest rates in trials of TCIs, followed by trials of the PDE4 inhibitor crisaborole and TCSs, although direct comparisons are not possible because of differences in study design. Tolerability issues in these clinical trials were generally mild to moderate and transient. This article also reviews published strategies for managing sensory tolerability issues in AD patients during treatment with topical therapies. Funding: Pfizer Inc., New York, NY.